2012
DOI: 10.2196/jmir.2148
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Evaluation of World No Tobacco Day in Latin America

Abstract: BackgroundWorld No Tobacco Day (WNTD), commemorated annually on May 31, aims to inform the public about tobacco harms. Because tobacco control surveillance is usually annualized, the effectiveness of WNTD remains unexplored into its 25th year.ObjectiveTo explore the potential of digital surveillance (infoveillance) to evaluate the impacts of WNTD on population awareness of and interest in cessation.MethodsHealth-related news stories and Internet search queries were aggregated to form a continuous and real-time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 48 publications
1
35
0
Order By: Relevance
“…The findings add to the growing literature on how novel data streams can inform education campaigns,20 21 public health22–26 and regulatory science 27. Findings demonstrated the possibility for real-time monitoring of education campaigns in the future.…”
Section: Resultsmentioning
confidence: 59%
“…The findings add to the growing literature on how novel data streams can inform education campaigns,20 21 public health22–26 and regulatory science 27. Findings demonstrated the possibility for real-time monitoring of education campaigns in the future.…”
Section: Resultsmentioning
confidence: 59%
“…Moreover, Internet sites can be mined to acquire data relevant to issues dealing with public health, a science referred to as infodemiology [24-26]. Several prior infodemiological-type studies have produced informative data related specifically to tobacco products [3,10,27]. E-cigarette forums have an increasingly popular presence on the Internet where e-cigarette users can post data relevant to the health effects they experience from using these products.…”
Section: Introductionmentioning
confidence: 99%
“…In the health and medical domain, much research has demonstrated the ability to understand real-world activity from search data including the detection of influenza [Eysenbach 2006;Ginsberg et al 2008;Santillana et al 2014], norovirus [Desai et al 2012], and dengue [Chan et al 2011] outbreaks; the discovery of side effects of medications [Yom-Tov and Gabrilovich 2013;; insights into healthcare utilization [White and Horvitz 2013b]; the study of dietary patterns [West et al 2013;Kusmierczyk et al 2015]; and measuring the effectiveness of public health awareness campaigns [Glynn et al 2011;Ayers et al 2012]. …”
Section: Search Log Analysismentioning
confidence: 99%